Pengaruh Work-Life Balance dan Green Human Resource Practices Terhadap Sustainability Performance Dimediasi Affective Commitment - Melida Wijaya; Retno Purwani Setyaningrum (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to examine the influence of work-life balance and green human resource practices on sustainability performance, with affective commitment as a mediating variable. The research was conducted on employees of Company XYZ located in Bekasi Regency. The respondents were employees of the company based in the Bekasi area. Since the total population was unknown, the sample size was determined using the Lemeshow formula with a 5% significance level, resulting in a sample size of 384 respondents. This study used primary data, which was collected through questionnaires. The data were analyzed using SmartPLS 3.0 to test validity, reliability, and path coefficients. The results indicate that both work-life balance and green human resource practices significantly influence sustainability performance, both directly and indirectly through affective commitment. Specifically, af-fective commitment strengthens the relationship between green human resource practices and sustainability performance, while it weakens the relationship between work-life balance and sustainability performance. These findings highlight the importance of enhancing em-ployees’ emotional engagement to support sustainability initiatives in the workplace.